hsa_circ_0000520 Serves as a Prognostic Biomarker for Colorectal Cancer and Promotes in the Disease Progression - Shi, Bingzhe; Lu, Xiufen; Ma, Wanli; Huang, Chao; Huo, Junyue (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Colorectal cancer (CRC) constitutes one of the prevalent malignancies within the gastrointestinal tract and serves as a primary contributor to cancer-related mortalities. This investigation sought to investigate the expression and prognostic significance of hsa_circ_0000520 in CRC and to evaluate its impact on the onset of CRC. Materials and Methods: The levels of hsa_circ_0000520 were measured via quantitative real-time polymerase chain reaction (qRTPCR). To delve into the mechanism through which circ_0000520 impacts CRC and to assess the cellular behavior of CRC cells, a series of experiments including the CCK-8, transwell assay, flow cytometer assay, cell cloning formation, dual-luciferase reporter assay, and bioinformatics method were performed. Results: The expression levels of hsa_circ_0000520 were markedly elevated in CRC cells and tissue specimens, and this elevation was correlated with a low survival rate. hsa_circ_0000520 affected CRC cell function via the miR-542-3p/MYH9 axis, thus exacerbating cancer progression. Conclusion: hsa_circ_0000520 functions as a predictive biomarker for the prognosis of CRC and participates in its progression. hsa_ circ_0000520 emerges as a new treatment strategy for CRC patients. Cite this article as: Shi B, Lu X, Ma W, Huang C, Huo J. Hsa_circ_0000520 serves as a prognostic biomarker for colorectal cancer and promotes in the disease progression. Turk J Gastroenterol. 2024;35(12):922-932.